Examining Health Disparities in Access to Mental Health Services in Urban and Rural Areas - Anita Putri; Rudi Hartono; Siti Nabila (International Journal of Health and Social Behavior, 2024)
This article investigates disparities in access to mental health services between urban and rural communities in Indonesia. By analyzing data on service availability, utilization, and barriers to access, the study highlights factors that contribute to unequal mental health support. Findings reveal that rural populations face greater challenges in accessing mental health care, primarily due to a lack of facilities, shortage of mental health professionals, and limited awareness. The results underscore the need for policies that address these geographic health disparities and promote equitable access to mental health services.